Small-molecule therapeutics for the treatment of glycolipid lysosomal storage disorders. - Butters, T; Mellor, H; Narita, K; Dwek, R; Platt, F (2003)
Glycosphingolipid (GSL) lysosomal storage disorders are a small but challenging group of human diseases to treat. Although these disorders appear to be monogenic in origin, where the catalytic activity of enzymes in GSL catabolism is impaired, the clinical presentation and severity of disease are heterogeneous. Present attitudes to treatment demand individual therapeutics designed to match the specific disease-related gene defect; this is an acceptable approach for those diseases with high frequency, but it lacks viability for extremely rare conditions. An alternative therapeutic approach termed 'substrate deprivation' or 'substrate reduction therapy' (SRT) aims to balance cellular GSL biosynthesis with the impairment in catalytic activity seen in lysosomal storage disorders. The development of N-alkylated iminosugars that have inhibitory activity against the first enzyme in the pathway for glucosylating sphingolipid in eukaryotic cells, ceramide-specific glucosyltransferase, offers a generic therapeutic for the treatment of all glucosphingolipidoses. The successful use of N-alkylated iminosugars to establish SRT as an alternative therapeutic strategy has been demonstrated in in vitro, in vivo and in clinical trials for type 1 Gaucher disease. The implications of these studies and the prospects of improvement to the design of iminosugar compounds for treating Gaucher and other GSL lysosomal storage disorders will be discussed.